Characteristics and risk factors for colorectal polyps among children in an urban area of Wenzhou, China: a retrospective case control study - Yinghui Wang; Lingjuan Fang; Kaiyu Huang; Tongtong Pan; Huajun Lu; Xiumei Yan (BMC, 2023)
Abstract Background Scarce evidence exists on pediatric colorectal polyp risk factors. This study explored the clinical manifestations, morphological and pathological characteristics of, and risk factors for pediatric colorectal polyps. Methods This retrospective case-control study included children who received colonoscopy, divided into a colorectal polyp group and a normal control group based on colonoscopy results. The risk factors for colorectal polyps in children were analyzed through logistic regression analysis. Results The mean age of children with polyps was 6.77 ± 3.44 years. Polyps were detected predominantly in males (72.9%); hematochezia was the primary clinical manifestation (80.25%). Most polyps were juvenile (88.9%) and solitary (87.7%); 50.6% were located in the rectosigmoid area. Univariate analysis showed that gender (P = 0.037), age (P < 0.001), family aggregation (P < 0.001), specific immunoglobulin E (sIgE) (P < 0.001), platelet count (P = 0.001), aspartate aminotransferase (AST) (P = 0.016), meat intake (P = 0.010), and vegetable intake (P < 0.001) were significantly associated with colorectal polyps. Age ≤ 6 years (3-6 years: OR: 26.601, 95% CI: 3.761-160.910; < 3 years: OR: 22.678, 95% CI: 1.873-274.535), positive family aggregation (OR: 3.540, 95% CI: 1.177-10.643), positive sIgE (OR:2.263, 95% CI: 1.076-4.761), and higher meat intake (OR:1.046, 95% CI: 1.029-1.063) were risk factors for pediatric colorectal polyps in logistic regression analysis. Higher vegetable intake (OR: 0.993, 95% CI: 0.986-1.000) was a protective factor against pediatric colorectal polyps. The area under the curve (AUC) of meat intake in the receiver operating characteristic (ROC) curve analysis for predicting colorectal polyps was 0.607; the best cut-off value was 92.14 g/d (P = 0.010, 95% CI: 0.527-0.687). The meat and vegetable intake combination AUC in predicting pediatric colorectal polyps was 0.781 (P < 0.001, 95% CI: 0.718-0.845). Conclusions Juvenile, solitary, and located in the rectosigmoid region polyps are most common in children. Hematochezia is the main clinical manifestation. Most polyps were, but multiple and proximally located polyps were also detected. Age ≤ 6 years, especially 3-6 years, positive family aggregation, positive sIgE, and higher meat intake are risk factors for pediatric colorectal polyps. A higher vegetable intake is a protective factor.